A study of thoracoabdominal injury of immature pigs restrained by various belts in front crashes. Issue 5 (3rd September 2019) - Wang, Qiaolin; Xiang, Hongyi; Guan, Sishu; Liao, Zhikang; Zhu, Xiyan; Yin, Zhiyong; Zhao, Hui
Abstract: To acknowledge better the thoracoabdominal injury of the paediatric restrained by the belts in front crashes, a total of 15 whole-body sled tests were performed, for 15 immature pigs corresponding to children aged 6 years old. The restraint methods were divided into three groups: Loading A, two parallel belts restraining chest and abdomen; Loading B, one diagonal belt and a lap belt; Loading C, double diagonal belts. Each subject experienced one test at an impact speed of 30 or 50 km/h, with a belt tension force sensor to determine the forces on chest, abdomen or diagonal belt. Detailed posttest necropsies were carried out for the animals post the test, and the thoracoabdomenal injuries were evaluated via the Abbreviated Injury Scale (AIS) and Injury Severity Score (ISS). The detected injuries were abrasion, contusion, laceration, bleeding and fracture. All animals sustained multi-injuries and the average ISS of the deaths was 37.0 ± 6.8. Lungs were injured most frequently, followed by spleens, and livers. The thorax experienced the MAIS 4 injuries at the chest belt forces ranging from 1.39 to 3.38 kN. The abdomen sustained the MAIS 2 injuries at the lap belt forces ranging from 0.97 to 1.26 kN, the MAIS 4 injuries from 3.07 to 3.43 kN. The chest MAIS 4 injuries occurred at the diagonal belt forces ranging from 1.88 to 2.50 kN, while the MAIS 4 at the forces from 3.13 to 3.44 kN. The results may be useful to learn the paediatric thoracoabdominal injuries, while the further studies concerning the paediatric injuries should be done in the future.